PENGARUH INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN UMKM (Studi Kasus Pada UMKM di Kelurahan Anaiwoi) - Hamsiani, Hamsiani; Turi, La Ode; Astaginy, Niar (Jurnal Akuntansi Kompetif, 2025)
This study aims to examine the influence of financial inclusion and financial literacy on the financial performance of MSMEs, as well as to determine whether financial behavior acts as a mediating variable in this relationship. The research uses a quantitative method with a descriptive-verificative approach and is conducted in Kelurahan Anaiwoi. Primary data were collected through questionnaires distributed to 52 MSME actors, with the sample size determined using Slovin’s formula. Data analysis was performed using multiple linear regression and the Sobel test with the assistance of SPSS version 25. The results show that financial inclusion and financial literacy have a positive and significant effect on financial behavior. Furthermore, financial inclusion, financial literacy, and financial behavior directly and significantly affect the financial performance of MSMEs. However, the Sobel test shows that financial behavior does not mediate the relationship between financial inclusion and financial literacy with MSME financial performance, so the mediation hypothesis is rejected. These findings highlight the importance of directly improving financial access and understanding to enhance MSME performance. Keywords: Financial Inclusion, Financial Literacy, Financial Behavior, Financial Performance, MSMEs